Positioning a Paediatric Compounded Non-Sterile Product Electronic Repository (pCNPeRx) within the Health Information Technology Infrastructure - Richard H. Parrish, II (MDPI AG, 2015)
Numerous gaps in the current medication use system impede complete transmission of electronically identifiable and standardized extemporaneous formulations as well as a uniform approach to medication therapy management (MTM) for paediatric patients. The Pharmacy Health Information Technology Collaborative (Pharmacy HIT) identified six components that may have direct importance for pharmacy related to medication use in children. This paper will discuss key positions within the information technology infrastructure (HIT) where an electronic repository for the medication management of paediatric patients' compounded non-sterile products (pCNP) and care provision could be housed optimally to facilitate and maintain transmission of e-prescriptions (eRx) from initiation to fulfillment. Further, the paper will propose key placement requirements to provide for maximal interoperability of electronic medication management systems to minimize disruptions across the continuum of care.